2022
DOI: 10.3389/fmicb.2022.913465
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Zhenwu decoction for the treatment of renal fibrosis at various stages: What is the role of Corynebacterium?

Abstract: Many studies demonstrated that Zhenwu decoction (ZWD) is effective in the treatment of kidney fibrosis, whereas the mechanism remains unclear. In this work, a microbiomics-based strategy was used to investigate the mechanism of protective effects of ZWD on kidney fibrosis. Unilateral ureteral obstruction was used to replicate a rat model of renal fibrosis, and rats were divided into prophylactic, early, and progression stages according to the timing of administration. Feces was collected to perform microbiota … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…In addition, Jiang et al reported that hyperlipidemia led to an extreme reduction in Bacteroidetes [33], which is consistent with our current results, and gratefully BT with EFT reversed this alteration. Bacteroidetes and Firmicutes which have a critical role in energy metabolism in the gut, and the F/B ratio, which is closely related to the metabolic capacity of the microbial community and inflammation, are important indicators of gut ecological dysregulation associated with the metabolic syndrome [50,51]. A significant increase in the ratio of F/B in HFFCD-induced hyperlipidemic mice was also observed in the present research, whereas supplementation with BT and EFT resulted in its essentially return to normal levels.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Jiang et al reported that hyperlipidemia led to an extreme reduction in Bacteroidetes [33], which is consistent with our current results, and gratefully BT with EFT reversed this alteration. Bacteroidetes and Firmicutes which have a critical role in energy metabolism in the gut, and the F/B ratio, which is closely related to the metabolic capacity of the microbial community and inflammation, are important indicators of gut ecological dysregulation associated with the metabolic syndrome [50,51]. A significant increase in the ratio of F/B in HFFCD-induced hyperlipidemic mice was also observed in the present research, whereas supplementation with BT and EFT resulted in its essentially return to normal levels.…”
Section: Discussionmentioning
confidence: 99%